Children Growing Up In Small Families And Their Social Adaptation - Ashuraliev, Rahmonjon (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This article provides a comprehensive and systematic scientific analysis of the social adaptation process of children growing up in small families. The study examines children’s adaptation to the school environment, emotional stability, level of self-control, and the formation of relationships with peers as key social indicators. The results of the study show that children growing up in small families usually have high rates of rapid adaptation to the educational process, management of their emotions, and independent decision-making. This is explained by the fact that parents provide their children with more individual attention, emotional support, and educational resources. At the same time, in some cases, these children may experience certain difficulties in communicating with peers, participating in group activities, and assuming social roles. This is explained by the limited daily social experience, in particular, with siblings. The conclusions drawn in the article serve to more effectively support the social development of children growing up in small families, to develop special programs aimed at developing social skills in educational institutions, and to formulate practical recommendations for parents. The results of this study are of significant theoretical and practical importance for scientific research in the fields of child psychology, pedagogy, and social development.